Delayed diagnosis of central skull-base osteomyelitis with abscess: case report and learning points - Chawdhary, G (Ann R Coll Surg Engl, 2017)
Central skull-base osteomyelitis (CSBO) is a rare life-threatening infection, usually resulting from medial spread of necrotising otitis externa. Here, we describe a case with no identifiable source of infection, causing a delay in diagnosis. An 80-year-old man with Crohn’s disease treated with mesalazine presented with collapse and tonic–clonic seizure. Computed tomography and magnetic resonance imaging showed a nasopharyngeal mass that was initially thought to be a neoplasm. Awaiting formal biopsy, he represented with collapse and repeat imaging showed features of abscess formation. Review of previous scans revealed skull-base erosion and the diagnosis was revised to skull-base osteomyelitis. This is the first reported case of CSBO associated with mesalazine use, an aminosalicylate used in Crohn’s disease. It is only the second reported case with abscess formation. We discuss the learning points in making a timely diagnosis and examine the potential association of factors such as mesalazine use and abscess formation in this case.